Examination of Hypotheses in Marketing Research - Ketevan, Maghlakelidze (British Journal of Marketing Studies, 2020)
Statistical data is derived based on the survey of respondents, in the following three areas of the Georgian consumer market: product prices, tuition fees in higher education, the number of people wishing to travel to the parts of Georgia. Using this marketing information, the task of examination hypotheses about the unknown average values ??of populations is solved.